2012
DOI: 10.1177/230949901202000216
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Marinum Infection of the Hand and Wrist

Abstract: Delayed antibiotic treatment of M marinum infections and steroid injections were associated with unsatisfactory outcome. Clinicians must have a high index of suspicion for this condition and avoid inappropriate management such as intralesional steroid injections. Public awareness to this condition should be raised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 11 publications
8
40
0
1
Order By: Relevance
“…The clinical picture of the patient is in agreement with the few cases elucidated in the literature [10]- [12]: nonspecific signs; a slow and chronic evolution; inflammatory signs discrete or absent. This insidious evolution becomes corollary of a chronicity which can be responsible for advanced lesions [13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The clinical picture of the patient is in agreement with the few cases elucidated in the literature [10]- [12]: nonspecific signs; a slow and chronic evolution; inflammatory signs discrete or absent. This insidious evolution becomes corollary of a chronicity which can be responsible for advanced lesions [13].…”
Section: Discussionsupporting
confidence: 88%
“…In literature [10]- [12] NTM tenosynovitis have been reported, but ours is unique because of its scope to five flexor tendons and the simultaneous combination of giant bursitis of wrist. Moreover bursitis wrist is still less exceptional topography and its association with rice bodies is another interest of this work.…”
Section: Discussionmentioning
confidence: 82%
“…Chen et al 8) reported 12 months of oral antibacterial therapy with CAM, EMB, and RFP without recurrences during an 18-month follow up. Cheung et al 16) reported a case series of 166 patients who had or were suspected of having Mycobacterium marinum infections. In this report, the mean duration of oral antibacterial therapy was 7.2 months; however, the duration of anti-bacterial therapy did not affect functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…2 Among patients with M. marinum tenosynovitis, poor functional outcomes are associated with delayed presentation and treatment with injectable steroids. 4 This case also highlights the importance of a thorough history for over-the-counter and traditional medications or other cultural remedies that might be contributing to the patient's presentation. In the case of our patient, manipulation of the area of injury with plant material and mild clinical response to itraconazole therapy indicated possible mixed infection with Sporothrix schenckii, but this was not proven on histopathology and cultures.…”
Section: Diagnosismentioning
confidence: 90%
“…This too is not an uncommon occurrence because the initial injury is often trivial, and the time between initial exposure and onset of clinical symptoms is often long. 1 Treatment delay is a risk factor for deep tissue infection, 3,4 reported in approximately one third of the cases. 2 Among patients with M. marinum tenosynovitis, poor functional outcomes are associated with delayed presentation and treatment with injectable steroids.…”
Section: Diagnosismentioning
confidence: 99%